12. Kerja Sama Indonesia-UNCTAD dalam Implementasi Competition Law and Policy di Indonesia Periode 2004-2007 - Priyatno, Dwi; Windiani, Reni; Putranti, Ika Riswanti (Journal of International Relations, 2017)
The monetary crisis that hit Indonesia in 1997 caused by various factors, one of the mainfactor was the practice of concentration of economic power that tend to for a monopolisticmarket. Thus, impacting the fragility of its economic resilience. In order to accelerate theeconomic growth after the monetary crisis, Indonesia had received financial assistancefrom the IMF, with the requirement that Indonesia had to restructure its economic systemas they agreed in the letter of intent. The letter of intent contains a point that Indonesiashall implement the competition law and policy to prevent the concentration of economicpower activities in Indonesia such as monopoly, cartel and bid rigging. In the process of itsimplementation, Indonesia had received assistance by UNCTAD to operate capacitybuilding for stakeholders. This research uses a perspective by neoliberal institutionalist toanalyze capacity building cooperation that conducted by Indonesia and UNCTAD. Thisresearch is descriptive analytic and also used qualitative as its research method. Theconclusion showed that cooperation by Indonesia and UNCTAD are based on rationality,which both sides took the benefit as they desired.